KARAKTERISASI EDIBLE FILM BERBAHAN DASAR GELATIN KULIT BABI SEBAGAI BAHAN PENGEMAS DAGING BABI - , Ir. Meity Sompie, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study consisted of three stages. The first stage was to determine the characteristics of pigskin gelatin with the use of animal age and acetic acid solution concentration on physical and chemical properties of pigskin gelatin. This study used Completely Randomized Design (CRD) with two factors and three replicates of treatments. The first factor was animal age consisting 3 levels (5, 7 and 9 months). The second factor was concentration of acetic acid solution consisting of 3 levels (2, 4 and 6 percents). The results showed that the application of animal age and concentration of acetic acid (CH3COOH) was highly significant (P <0.01) on the characteristics of gelatin. The second stages of research was to determine the comparisons between species and concentration of plasticizer. This study used Completely Randomized Design (CRD) with two factors, the first factor was different plasticizer (glycerol, sorbitol and PEG), the second factor was concentration of plasticizer (40.60 and 80%). The interaction between the use of different plasticizer and concentrations of plasticizer was highly significant (P <0.01) to the value of the water vapor transmission rate (WVTR) of edible film, but it had no significant effect (P> 0.05) on the thickness, tensile strength, elongation and water content of edible film. The third stages of the study, was determine the application of edible coating as a packing of pork and it also used Completely Randomized Design (CRD) with two factors and three replications, gelatin 0, 10 and 20% and time of cold storage temperatures, 0, 3 and 6 days, The results showed that the edible coating was combination of pigskin produces the better characteristics of pork. It was concluded that the pig skin gelatin from 7 months and 2 % acetic acid can be used as raw material for edible films and can be applied as an edible coating on fresh pork with cold temperature storage up to 6 days.